2007
DOI: 10.1007/s00213-007-1027-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between core body temperature and 3,4-methylenedioxymethamphetamine metabolism in rats: implications for neurotoxicity

Abstract: This is the first report showing a direct relationship between core body temperature and MDMA metabolism. This finding has implications on both the temperature dependence of the mechanism of MDMA neurotoxicity and human use, as hyperthermia is often associated with MDMA use in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 49 publications
4
49
1
Order By: Relevance
“…These results, which are consistent with those of Escobedo et al (2005), suggest that HHMA and HMMA do not readily penetrate the blood-brain barrier (either in their free form or as sulfate or glucuronic conjugates) and indicate that there is little or no brain metabolism of MDMA to HHMA or HMMA. Taken together, these observations and (Steele et al, 1991;Escobedo et al, 2005) cast doubt on the view that HHMA and HMMA are directly involved in MDMA neurotoxicity (Goni-Allo et al, 2008) but leave open the possibility that MDA or a catechol-thioether metabolite of MDMA might be involved.…”
Section: Resultsmentioning
confidence: 97%
“…These results, which are consistent with those of Escobedo et al (2005), suggest that HHMA and HMMA do not readily penetrate the blood-brain barrier (either in their free form or as sulfate or glucuronic conjugates) and indicate that there is little or no brain metabolism of MDMA to HHMA or HMMA. Taken together, these observations and (Steele et al, 1991;Escobedo et al, 2005) cast doubt on the view that HHMA and HMMA are directly involved in MDMA neurotoxicity (Goni-Allo et al, 2008) but leave open the possibility that MDA or a catechol-thioether metabolite of MDMA might be involved.…”
Section: Resultsmentioning
confidence: 97%
“…Consistent with this view, administration of the COMT inhibitor entacapone 30 min before MDMA dosing to rats exacerbates the 5-HT depletion produced by MDMA, an effect not related either to changes on core body temperature, because the MDMA-induced hyperthermic response was not significantly altered, or to the serum L-tyrosine levels, which where higher in the MDMA-treated rats than inn the MDMA/entacapone-treated rats, suggesting that toxic MDMA catechol metabolites are responsible for the MDMA toxicity in the entacapone-treated rats (Goñi-Allo et al, 2008a). Moreover, although the HMMA and HMA plasma concentrations were significantly lower in the entacapone-treated animals, plasma concentrations of HHMA and HHA were unchanged, suggesting that these compounds are cleared by alternative pathways (Goñi-Allo et al, 2008b), for example, thioether adduct formation. Taken together, these results support the idea that the COMT activity level may be relevant in terms of susceptibility to MDMA neurotoxicity.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies showed that HHMA and HMMA are formed in vivo after MDMA administration in both rats and humans (Lim et al, 1992;Segura et al, 2001;Valtier et al, 2007;Goni-Allo et al, 2008;Kolbrich et al, 2008b;Mueller et al, 2009), but there is uncertainty about whether these hydroxylated metabolites represent major MDMA metabolites in rodents. Here we observed that AUCs for HHMA and HMMA were always greater than AUC for MDMA in rats given 2.5 mg/kg, confirming that O-demethylenation is the predominant pathway for biotransformation in rats given clinically relevant MDMA doses.…”
Section: Discussionmentioning
confidence: 99%